1996
DOI: 10.1021/jp961076d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polarizability on the Hydration of the Chloride Ion

Abstract: Polarizable and nonpolarizable potential models for both water and chloride are used to address the issue of surface Vs interior solvation of the chloride ion in Cl(H 2 O) n -clusters, for n up to 255. We find that, even for the largest clusters, simulations with polarizable water models show that the chloride ion is preferentially solvated near the surface of the cluster. This behavior is not observed with a nonpolarizable model. The many-body effects are not directly responsible for this solvation behavior; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
291
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(326 citation statements)
references
References 54 publications
19
291
0
4
Order By: Relevance
“…Accurate simulations of ion solvation require polarizable force fields (12,16,(33)(34)(35). Here we applied the polarizable models of Lamoureux et al for water (SWM4-DP) (20) and for ions (21); these ion models were parameterized in conjunction with the SWM4-DP water model.…”
Section: Methodsmentioning
confidence: 99%
“…Accurate simulations of ion solvation require polarizable force fields (12,16,(33)(34)(35). Here we applied the polarizable models of Lamoureux et al for water (SWM4-DP) (20) and for ions (21); these ion models were parameterized in conjunction with the SWM4-DP water model.…”
Section: Methodsmentioning
confidence: 99%
“…1 However, a combination of computational [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and experimental studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] has shown that ions can reside and even be enhanced at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…To keep the study of different methods ͑and ion-molecule systems͒ within a manageable limit, we will restrict to cases where all polarizable species ͑ion and molecule͒ are modeled with the same method. Indeed one could treat each polarizable site with different methods 55 but it is to be expected that, given the essentially similar nature of the various methods available, such approach would not change the essence of our conclusions. Therefore, in this study we compare the accuracy of PD and SH methods, applying them to the whole ion-molecule system.…”
Section: Introductionmentioning
confidence: 99%